Energy efficiency of the accumulation wall with a transparent insulation - Świrska-Perkowska Jadwiga; Jęglet Karolina (MATEC Web of Conferences, 2018)
This paper presents a numerical model of an accumulating solar wall with transparent insulation (ASW-TI). The objective of the simulation was to evaluate the energy efficiency of ASW-TI for different climatic conditions in Poland, i.e. for high, medium, and low irradiation. For each climate, the calculations were made for the entire heating period. As a result, temperature distributions in a wall at different times of the process and the energy balance of the wall in particular months and during the entire heating period were obtained.